Letter to the Editors - Tsigaris, Panagiotis (Journal of Scholarly Publishing, 2019)
JSP does not routinely publish letters to the editor, but given the strong responses pro and con to Derek Pyne’s controversial ‘The Rewards of Predatory Publications at a Small Business School’ (48.3), we have decided to allow a one-time rejoinder to the statistical analysis it offered. Given the differences in classical regression analysis and one applied to a case study, both the article and the letter have their respective merits. Readers will decide for themselves which conclusion to accept.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMzEzOC9qc3AuNTAuMi4wNQ